Myc‐dependent endothelial proliferation is controlled by phosphotyrosine 1212 in VEGF receptor‐2. (23rd September 2019) - Testini, Chiara; Smith, Ross O; Jin, Yi; Martinsson, Pernilla; Sun, Ying; Hedlund, Marie; Sáinz‐Jaspeado, Miguel; Shibuya, Masabumi; Hellström, Mats; Claesson‐Welsh, Lena
Abstract: Exaggerated signaling by vascular endothelial growth factor (VEGF)‐A and its receptor, VEGFR2, in pathologies results in poor vessel function. Still, pharmacological suppression of VEGFA/VEGFR2 may aggravate disease. Delineating VEGFR2 signaling in vivo provides strategies for suppression of specific VEGFR2‐induced pathways. Three VEGFR2 tyrosine residues (Y949, Y1212, and Y1173) induce downstream signaling. Here, we show that knock‐in of phenylalanine to create VEGFR2 Y1212F in C57Bl/6 and FVB mouse strains leads to loss of growth factor receptor‐bound protein 2‐ and phosphoinositide 3′‐kinase (PI3K)p85 signaling. C57Bl/6 Vegfr2 Y1212F/Y1212F show reduced embryonic endothelial cell (EC) proliferation and partial lethality. FVB Vegfr2 Y1212F/Y1212F show reduced postnatal EC proliferation. Reduced EC proliferation in Vegfr2 Y1212F/Y1212F explants is rescued by c‐Myc overexpression. We conclude that VEGFR2 Y1212 signaling induces activation of extracellular‐signal‐regulated kinase (ERK)1/2 and Akt pathways required for c‐Myc‐dependent gene regulation, endothelial proliferation, and vessel stability. Synopsis: Previously uncharacterized VEGFR2 phosphorylation at Y1212 promotes endothelial proliferation and vessel stability by a mechanism involving Erk1/2, Akt and c‐Myc dependent transcriptional regulation. Phosphorylated VEGFR2 Y1212 binds GRB2 and PI3Kp85, and mediates activation of ERK1/2 and Akt signaling. Reduced EC proliferation in Vegfr2 Y1212F explants is rescued by c‐Myc overexpression. Vegfr2 Y1212F mutant mice are unable to activate c‐Myc, display suppressed endothelial cell proliferation and vascular deficiency. Vegfr2 Y1212F mutation in the C57Bl/6 background leads to partial embryonic lethality. Vegfr2 Y1212F mutation in the FVB background results in vascular deficiency in the postnatal stage only. Abstract : Previously uncharacterized VEGFR2 phosphorylation at Y1212 promotes endothelial proliferation and vessel stability by a mechanism involving Erk1/2, Akt and c‐Myc dependent transcriptional regulation.